Searching for Researchers: an Ontology-based NoSQL Database System Approach and Practical Implementation - A. Salgueiro, Mariana D.; dos Santos, Veronica; C. Rêgo, André L.; Guimarães, Daniel S.; Santos, Jefferson B.; H. Haeusler, Edward; V. Villas, Marcos; Lifschitz, Sérgio (Journal of Information and Data Management, 2022)
This work presents the design and implementation of two web-based search systems, Busc@NIMA and Quem@PUC. Both systems allow the identification of research and development projects, besides existing competencies in laboratories and departments involving professors and researchers at PUC-Rio University. Our applications are based on a list of search-related terms that are matched to the dataset composed of PUC-Rio’s Lattes CVs offered courses, information from administrative systems, and specific keywords that are input by the professors/researchers themselves. To integrate all the needed data, we consider multiple database and search technologies, such as XML, RDF, TripleStores, and Relational Databases. Search results include professor’s name, academic papers, teaching activities, contact links, keywords, and laboratories of those involved with the subject represented by the set of keywords input. We describe the main features that show how our systems work.